Gaming, States and Tax Revenues - The Tortoise or the Hare: A CGE Comparative Assessment of Casino Resorts and Racinos - Michael Lahr; Maria Alvarez (European Regional Science Association (ERSA), 2013)
State tax revenues from casinos as a share of total state gaming revenues generally correlate well with the year of legalization. The share ranges from about 8.0 percent in Nevada, the first state to legalize gambling, to 47.4 percent in Pennsylvania, one of the most recent state to legalize gambling. As a result, even though Nevada's agglomeration of gaming remains the largest within the U.S., its direct state revenues from that industry are now dwarfed by those of recent state entrants. Theoretically speaking, such heavy tax rates should dampen growth of the casino revenues in states that adopt them. Indeed, states with lower tax rates do, in fact, tend to have larger gaming revenue streams: This suggests more jobs and income are generated directly by the gaming industry when lower tax rates are applied. This paper, therefore, probes the size of the indirect economic activity that would have to be generated through spending of casinos on state-based labor and vendors in order to offset the benefits states could obtain if they simply applied a higher direct tax rate on gaming. This issue is examined through the lens of the New Jersey casino resort industry.
Keywords: 330; COMPUTABLE GENERAL EQULIBRIUM; CASINO GAMING; REGIONAL SAM